Sarai como esposa e irmã de Abrão: um estudo exegético de Gn 12,10-13,1a - Dias, Elizangela Chaves (2011)
This paper aims to present an exegetical study of a biblical narrative: the Genesis 12,10-13,1a. It follows the style of commentary. The research advances with the biblical tradition in question. In each chapter two investigations are carried out. 1) a linguistic and literary study which includes translation, morphological analysis, syntactic, stylistic and narrative; and 2) a historical-theological that serves as a research on the historical and cultural context, as well as, the theology in the text. In this sense, this research has hypothesized the question: 'Sarai as wife and sister of Abraham'. Throughout the study it is possible to visualize a growing understanding of the scope of the term 'wife and sister'. Based on the arguments found, adding reflections on historical-archaeological and biblical-theological, it seems plausible to say that Sarai is Abraham´s wife and sister not only in the denotative sense, but also in a metaphorical one. Moreover, this expression becomes a key to the interpretation as 'sister' and 'wife' that are important characters in the theological and symbolic language of the bible